Intervindo na falha da coleta de dados para análise e disseminação da informação no município de Santo Antônio de Posse - Lins, Adilson Araújo; Ramos, Claudia Rielli; Conti, Edilaine Tais Oliveira Lima; Moro, Jaísa Valéria; Simentom, Márcia Cristina Antônio; David, Marina Leitão; Madi, Paulo Cesar; Corrêa, Rosângela Zabaleta Alves; Ferreira, Sandro Sebastião; Alberto, Valeria Mileo F. Corrêa; et al. (Revista Acadêmica GUETO, 2024)
Projeto